Shared Capacity and Levelized Cost with Application to Power-to-Gas Technology - Gunther Glenk (ZBW - Leibniz-Informationszentrum Wirtschaft, 2019)
The calculation of unit cost that can be used for estimating capacity investment decisions is frequently ambiguous due to the many ways to apportion applicable cash ows connected to the delivery of products. This paper studies the identification of relevant unit cost when productive capacity is shared among multiple outputs. Building upon the concept of levelized product cost, I find that unit cost should re ect a constant revenue payment required to break-even on the initial investment. This payment, which is shown to depend on the perspective that an investor can assume, determines the aggregation of upfront capacity expenditures with periodic operating expenses to the relevant cost and unit. I apply the framework to examine new Power-to-Gas technology, which could become a central enabler of the transition towards a sustainable economy by reversibly converting electricity to hydrogen. Contrary to the common belief that fossil fuels are indispensable, my analysis shows that reversible Power-to-Gas will be sufficiently competitive with alternative fossil-based energy sources so as to provide a clean solution to the challenges of intermittent renewable electricity and widespread industrial decarbonization.
Keywords: M41; 330; unit cost; capacity investment; product prices; renewable energy; energy storage